Relation of anxiety and pulse rate before tooth exctraction of 6-9 years old children - De Hersa, Sarah Cinthia Richy Artha; Herdiyati, Yetty; Tjahajawati, Sri (Padjadjaran Journal of Dentistry, 2012)
Introduction: Anxiety in children during dental treatment is a common problem that affects the success of dental care. Only a few patients come to the dentist without anxiety and it will be far more difficult for dentists to provide satisfactory dental care for tense patients compared to patients who are relaxed and cooperative.The purpose of this study was to analized relationship of the anxiety in children  with pulse rate aged 6-9 years old before tooth extraction. Methods: This method of this study was descriptive with a sample of 30 children aged 6-9 years old. The samples collected by using purposive sampling at the first time they would get dental extraction treatment. Measurement used questionnaire with Corah method and measure their pulse before tooth extraction. Results: The result shows in 30 children aged 6-9 years old who first came to the dentist there are 90% children who have no anxiety, 3,3% children who have high anxiety, and 6,7% children who have highest anxiety. The result of statistical analysis of obtained p-value is 0,001 less than 0,05 indicating a significant relationship between anxiety and pulse rate of children before tooth extraction. Conclusion:  There is strong relationship of the anxiety with the child’s pulse before tooth extraction of 6-9 year old children.